Fungi and lignocellulosic biomass - Kubicek, C. P. (Christian P.) (Ames, Iowa : Wiley-Blackwell, 2013)
Fungi and Lignocellulosic Biomass offers a comprehensive review of the use of fungi in efficient and cost-effective conversion of cellulosic biomass into fuel. Complete, up-to-date coverage ranges from the biochemical basis of cellulose degradation by fungi to the application of key fungal enzymes in the biofuel industry. The enzymology of cellulose, hemicelluloses, and lignin degradation are all examined. Written by a leading researcher in the field, this book is a valuable tool for researchers, engineers, and industry professionals interested in advancing the development and production of bi.
The plant biomass -- The actors : plant biomass degradation by fungi -- The tools, part 1 : enzymology of cellulose degradation -- The tools, part 2 : enzymology of hemicellulose degradation -- The tools, part 3 : enzymology of lignin degradation -- Catabolic pathways of soluble degradation products from plant biomass -- Regulation of formation plant biomass-degrading enzymes in fungi -- The fungal secretory pathways and their relation to lignocellulose degradation -- Production of cellulases and hemicellulases by fungi -- Production of fermentable sugars from lignocelluloses -- Lignocellulose biorefinery.
Includes bibliographical references (pages 231-284) and index.
Print version record.
Keywords: Lignocellulose -- Biodegradation; Fungi -- Biotechnology; Biomass energy; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Biomass energy; Fungi -- Biotechnology; Lignocellulose -- Biodegradation; Electronic books; Electronic books